(3JaQjL GdcQhH aj JOHjQ GdMQhHs ((3CHh GdaVd Hf YHO GdhgGH GdSfHGWi s)
(3ChdgG (B:s
(3hHYO adeG cGf GdSdWGf CHh GdSYGOGJ aQL Hf GdSdWGf aQL Hf GdSdWGf CHj SYjO HQbhb s
(3BNQgG (B:s
(3MVhQ ef jJb Hg Gdedc ef GdefOhHjf dPdc , hGddg CYde s
(3fSNI NRGFfjIs
(3Gda ddedc GdfGUQ aQL Hf HQbhbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B13 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs